Mining key genes related to root morphogenesis through genome-wide identification and expression analysis of RR gene family in citrus - Zhang, Manman; Wang, Fusheng; Wang, Xiaoli; Feng, Jipeng; Yi, Qian; Zhu, Shiping; Zhao, Xiaochun (Frontiers in Plant Science, 2022)
Morphogenesis of root is a vital factor to determine the root system architecture. Cytokinin response regulators (RRs) are the key transcription factors in cytokinin signaling, which play important roles in regulating the root morphogenesis. In this study, 29 RR proteins, including 21 RRs and 8 pseudo RRs, were identified from the genome of citrus, and termed as CcRR1-21 and CcPRR1-8, respectively. Phylogenetic analysis revealed that the 29 CcRRs could be classified into four types according to their representative domains. Analysis of cis-elements of CcRRs indicated that they were possibly involved in the regulation of growth and abiotic stress resistance in citrus. Within the type A and type B CcRRs, CcRR4, CcRR5, CcRR6 and CcRR16 highly expressed in roots and leaves, and dramatically responded to the treatments of hormones and abiotic stresses. CcRR2, CcRR10, CcRR14 and CcRR19 also highly expressed in roots under different treatments. Characteristic analysis revealed that the above 8 CcRRs significantly and differentially expressed in the three zones of root, suggesting their functional differences in regulating root growth and development. Further investigation of the 3 highly and differentially expressed CcRRs, CcRR5, CcRR10 and CcRR14, in 9 citrus rootstocks showed that the expression of CcRR5, CcRR10 and CcRR14 was significantly correlated to the length of primary root, the number of lateral roots, and both primary root and the number of lateral roots, respectively. Results of this study indicated that CcRRs were involved in regulating the growth and development of the root in citrus with different functions among the members.